The expression of prostaglandins-related genes in erythrocytes of broiler chicken responds to thiram-induced tibial dyschondroplasia and recombinant glutathione-S-transferase A3 protein. (June 2019) - Niu, S.; Wang, C.X.; Jia, F.J.; Jahejo, A.R.; Li, X.; Ning, G.B.; Zhang, D.; Ma, H.L.; Hao, W.F.; Gao, W.W.; Zhao, Y.J.; Gao, S.M.; et al.
Abstract: Tibial dyschondroplasia (TD) is a type of bone deformity found in fast-growing chickens, which induce inflammatory responses. Prostaglandins (PGs) implicate in bone formation and bone resorption, associated with inflammation in an autocrine/paracrine manner. This study used qRT-PCR and immunohistochemistry analysis to identify the expression patterns of PG-related genes in the erythrocytes of broiler chickens and explore the effects of thiram-induced TD and the recombinant glutathione-S-transferase A3 (rGSTA3) protein on the expression of PG-related genes: GSTA3, cyclooxygenase 2 (COX-2), prostaglandin D2 synthase (PTGDS), prostaglandin E synthase (PTGES), prostaglandin E2 receptor (PTGER) 3, PTGER4 and prostaglandin reductase 1 (PTGR1). Interestingly, the results showed that these seven PG-related genes expression was identified in the erythrocytes of broiler chicken, and thiram-induced TD suppressed the expression of these PG-related genes in the initial stage of TD and promoted their expression in TD recovery. These findings demonstrated that the immunoregulatory function of erythrocytes can be inhibited in the early stage of TD and promoted in the recovery stage by modulating the expression of PG-related genes. Further, the rGSTA3 protein can modulate the expression of PG-related genes in erythrocytes and participate in the recovery of TD. Highlights: The expression of 7 types of prostaglandins-related genes was identified in chicken erythrocytes. The expression of prostaglandins-related genes in erythrocytes is highly related to the development of TD. The rGSTA3 protein can modulate the expression of prostaglandins-related genes in erythrocytes.